Kohesi dalam Tajuk Rencana pada Laman Berita Kompas.id dan Implementasinya sebagai Bahan Ajar Kebahasaan Teks Editorial di SMA - Rahmawati, Fatih; Ekawati, Mursia; Asmara, Rangga (Kajian Bahasa dan Sastra (KABASTRA), 2024)
Cohesion is an important aspect in creating cohesiveness in a discourse, including editorial discourse. In Kompas.id's editorials, there are also many signs of cohesion. This indicates that the discourse is a coherent and complete discourse. The aim of this research is to describe the grammatical cohesion and lexical cohesion used in the editorials on the November 2023 edition of the Kompas.id news page. This research uses a qualitative descriptive method. Data collection techniques use listening methods and note-taking techniques. The data analysis technique uses the agih method with basic techniques for direct elements (BUL) and advanced techniques for reading marks, replacement techniques, and expansion techniques. The results of this research show that in the editorials on the November 2023 edition of the Kompas.id news page, grammatical cohesion was found in the form of references, substitutions, eliminations, conjunctions and lexical cohesion in the form of repetition, synonymy, antonymy, collocation, hyponymy and equivalence. The results of this research can also be implemented as linguistic teaching material for class XII high school editorial texts.